Direct‐Acting Antivirals in Hepatitis C Virus‐Associated Diffuse Large B‐cell Lymphomas. (14th December 2018) - Merli, Michele; Frigeni, Marco; Alric, Laurent; Visco, Carlo; Besson, Caroline; Mannelli, Lara; Di Rocco, Alice; Ferrari, Angela; Farina, Lucia; Pirisi, Mario; Piazza, Francesco; Loustaud‐Ratti, Véronique; et al.
Abstract: Background: International guidelines suggest hepatitis C virus (HCV) eradication by direct‐acting antivirals (DAAs) after first‐line immunochemotherapy (I‐CT) in patients with HCV‐positive diffuse large B‐cell lymphoma (DLBCL), although limited experiences substantiate this recommendation. Moreover, only a few data concerning concurrent administration of DAAs with I‐CT have been reported. Subjects, Materials, and Methods: We analyzed hematological and virological outcome and survival of 47 consecutive patients with HCV‐positive DLBCL treated at 23 Italian and French centers with DAAs either concurrently (concurrent cohort [ ConC ]: n = 9) or subsequently (sequential cohort [ SeqC ]: n = 38) to first‐line I‐CT (mainly rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone [R‐CHOP]‐like). Results: Median age was 61 years, 89% of patients had stage III/IV, and 25% presented evidence of cirrhosis. Genotype was 1 in 56% and 2 in 34% of cases. Overall, 46 of 47 patients obtained complete response to I‐CT. All patients received appropriate DAAs according to genotype, mainly sofosbuvir‐based regimens ( n = 45). Overall, 45 patients (96%) achieved sustained virological response, 8 of 9 in ConC and 37 of 38 in SeqC . DAAs were well tolerated, with only 11 patients experiencing grade 1–2 adverse events. Twenty‐three patients experienced hepatic toxicity (grade 3–4 in seven) following I‐CT in SeqC, compared to only one patient in ConC . At a median follow‐up of 2.8 years, two patients died (2‐year overall survival, 97.4%) and three progressed (2‐year progression‐free survival, 93.1%). Conclusion: Excellent outcome of this cohort of HCV‐positive DLBCL suggests benefit of HCV eradication by DAAs either after or during I‐CT. Moreover, concurrent DAAs and R‐CHOP administration appeared feasible, effective, and ideally preferable to deferred administration of DAAs for the prevention of hepatic toxicity. Abstract : Epidemiological studies have established that hepatitis C virus (HCV) is associated with diffuse large B‐cell lymphoma (DLBCL). This article reports on patients with HCV‐positive DLBCL treated with direct‐acting antivirals either concurrently or subsequently to a curative‐intent first‐line immunochemotherapy.